MEDIATING EFFECT OF TOURIST MOTIVATION TO THE REVISIT INTENTION IN TREKKING SENTUL - Maya Syafriana Effendi; Nana Trisnawati; Euis Puspita Dewi; Rilla Sovitriana; Siti Komsiah; I Gede Agus Suwartane (UNIVERSITAS INDRAPRASTA PGRI, 2022)
Sentul Trekking Tourism Object is a tourist destination that offers natural beauty along with physical activities. The phenomenon based on the destination information of tourists visiting the Sentul Trekking tourist destination increased at the beginning of 2022. This study uses an associative quantitative method. The sample taken amounted to 44 respondents who were calculated using incidental purpose sampling. Collecting data using a questionnaire consisting of statements that cover all research variables. Respondents' answers to these statements were then analyzed using the partial least square method using the Smart PLS ver.3.0 software for Windows and SPSS version 25. The results showed that: there is not an effect of service quality on tourist motivation, there is an effect of service quality on revisit intention, there is an effect of marketing communication on tourist motivation, there is an effect of marketing communication on Revisit Intention, and there is an effect of Tourist motivation on Revisit Intention. The intervening variable of Tourist motivation did not mediate the variables of Service quality on Revisit Intention but the tourist motivation mediated the variables Marketing communication on Revisit Interest in the Trekking Sentul